Polyphase Mid‐Latitude Glaciation on Mars: Chronology of the Formation of Superposed Glacier‐Like Forms from Crater‐Count Dating. Issue 2 (25th February 2020) - Hepburn, A. J.; Ng, F. S. L.; Livingstone, S. J.; Holt, T. O.; Hubbard, B.
Abstract: Reconstructing Mars's glacial history informs understanding of its physical environment and past climate. The known distribution of viscous flow features (VFFs) containing water ice suggests that its mid‐latitudes were glaciated during the Late Amazonian period (the last several hundred million years). The identification of a subgroup of VFFs—called superposed glacier like forms (SGLFs)—flowing onto other VFFs, indicates multiple glacial phases may have occurred during this time. To explore the history and spatial extent of these glaciations, we record the distribution of SGLFs globally and use impact‐crater counting to date the SGLFs and the VFFs onto which they flow. Our inventory expands the handful of SGLFs reported in earlier literature to include 320 located throughout the mid‐latitudes. Our dating reveals these SGLFs to be much younger than their underlying VFFs, which implies a spatially‐asynchronous glaciation. SGLFs have been forming since ∼65 Ma, and their ages are clustered in two distinct groups around 2–20 and 45–65 Ma, whereas the ages of their underlying VFFs span the last ∼300 Ma diffusely. We discuss these results in the light of well‐known uncertainties with the crater‐dating method and infer that while ice sheets decayed over the Late Amazonian period, alpine glaciers waxed and waned in at least two major cycles before their final demise approximately two million years ago. Plain Language Summary: Mars hosts numerous ice‐rich glacier‐like landforms throughout its mid‐latitudes. Previously recognised high‐alpine glaciers superposed over lower elevation valley glaciers have been assumed to correspond to multiple episodes of mid‐latitude glaciation. However, these superposed glaciers have not been dated, and so the timing of their formation is unknown. Here, we conduct a Mars‐wide survey of superposed high‐alpine glaciers. We retrieve a formation age for each of them by counting the number of impact craters on their surface, as well as those on the underlying valley glacier. We find 320 examples of glaciers superposed over valley glaciers. The oldest superposed glaciers formed approximately 65 million years ago and the (many) remaining superposed glaciers formed in two distinct subsequent periods. These results suggest at least two major cycles of alpine glaciation in Mars's recent geological history. Finally, our data suggest that mid‐latitude glaciation on Mars ended about two million years ago. Key Points: The first complete inventory of 320 martian 'superposed glacier‐like forms' (SGLFs), which flow onto other viscous flow features, is presented Formation ages of SGLFs derived from their impact‐cratering records cluster in two groups (2–20 Ma, 45–65 Ma) and are much younger than formation ages of the underlying viscous flow features Martian alpine glaciers experienced two cycles of growth and recession before their final demise a few million years ago